The ERF transcription factor MdERF38 promotes drought stress‐induced anthocyanin biosynthesis in apple - An, Jian‐Ping; Zhang, Xiao‐Wei; Bi, Si‐Qi; You, Chun‐Xiang; Wang, Xiao‐Fei; Hao, Yu‐Jin (The Plant journal : for cell and molecular biology, 2020)
SUMMARY Drought stress induces anthocyanin biosynthesis in many plant species, but the underlying molecular mechanism remains unclear. Ethylene response factors (ERFs) play key roles in plant growth and various stress responses, including affecting anthocyanin biosynthesis. Here, we characterized an ERF protein, MdERF38, which is involved in drought stress‐induced anthocyanin biosynthesis. Biochemical and molecular analyses showed that MdERF38 interacted with MdMYB1, a positive modulator of anthocyanin biosynthesis, and facilitated the binding of MdMYB1 to its target genes. Therefore, MdERF38 promoted anthocyanin biosynthesis in response to drought stress. Furthermore, we found that MdBT2, a negative modulator of anthocyanin biosynthesis, decreased MdERF38‐promoted anthocyanin biosynthesis by accelerating the degradation of the MdERF38 protein. In summary, our data provide a mechanism for drought stress‐induced anthocyanin biosynthesis that involves dynamic modulation of MdERF38 at both transcriptional and post‐translational levels. Significance Statement MdERF38 promotes anthocyanin biosynthesis by interacting with MdMYB1 and enhancing the binding of MdMYB1 to its target genes in response to drought stress. MdBT2 decreases drought‐induced anthocyanin accumulation by accelerating the degradation of MdERF38.